Using social media as a tool for business improvement and certification of knowledge workers. Issue 9 (31st July 2014) - Colomo‐Palacios, Ricardo; Messnarz, Richard; Siakas, Kerstin; Palosi, Daniel; Coakley, Darragh; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT Business improvement is a hot topic in all business areas. In the last years, the unstoppable emergence of the use of social media by organizations and individuals alike has opened this tool for knowledge networking purposes. In this paper, the authors shed some light on how the traditional knowledge management approach has changed to a networked approach of knowledge sharing. Authors also explain how social media is used as a business tool, in particular in Information Technology industry environments. ECQA Certified Social Media Networker Skills (SIMS) is a new qualification that is available from 2013 and is meant to train and certify experts in the use of social media as a business improvement enabler and as a means for knowledge networking in organizational settings. Copyright © 2014 John Wiley & Sons, Ltd.